Industrial Commercialization in the Midst of the Spirit of Do It Yourself in the Underground Music Scene: Analysis of Vincent Mosco's Communication Political Economy Concept on the Television Program "DCDC Musikkita" - Suryana, Mohammed Aden (Social Science Studies, 2025)
This study explores the tension between the Do It Yourself (DIY) ethos of the underground music scene and the forces of commercialization, focusing on the Indonesian television program DCDC Musikkita. The DIY principle, rooted in independence and resistance to mainstream commercialization, has long defined underground music. However, the rise of digital platforms and corporate sponsorships has introduced new challenges, as indie musicians navigate the pressures of market demands while striving to maintain artistic integrity. Using a qualitative case study approach, this research analyzes the commercialization of the underground music scene through Vincent Mosco's Political Economy of Communication framework. The findings reveal that while digital platforms and corporate sponsorships offer indie musicians opportunities for greater exposure and financial gain, they also risk eroding the DIY values that underpin the scene. The study highlights the dilemma faced by musicians in balancing artistic autonomy with the need to adapt to market-driven imperatives. Ultimately, the research underscores the complex interplay between commercialization and cultural resistance, emphasizing the need for indie musicians to find a balance between leveraging market opportunities and preserving their artistic integrity in an increasingly commercialized industry.